Conjuntos minimais e caóticos em campos de vetores planares suaves por partes - Gazetta, Daniele Alessandra Reghini [UNESP] (2016)
The main result of this work is the Poincaré - Bendixson Theorem for planar piecewise smooth vector fields, which tell us what kind of limit sets arise in this context. We will also study details about the concepts of minimal and chaotic sets in planar piecewise smooth vector fields.